2019
DOI: 10.1097/meg.0000000000001388
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of occult hepatitis B virus infection in hepatitis C virus-associated hepatocellular carcinoma

Abstract: Background Occult hepatitis B virus infection (OBI) frequently occurs in patients with chronic hepatitis C (CHC) infection, but the influence of OBI on CHC outcome is still uncertain. The aim of the present study was to clarify the clinical and pathological characteristics of OBI in CHC-related hepatocellular carcinoma (HCC). Patients and methods DNA was obtained from serum and tumor tissue of patients with hepatitis C virus (HCV)-related HCC with negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…While there were no clinical differences between patients with and without OBI (gender, serum transaminases, platelet count, albumin, bilirubin, prothrombin time, alphafetoprotein, Child-Pugh score), those with OBI were younger (48.4 year-old for OBI compared to 51.4 year-old for non-OBI), and were associated with more advanced histological grades of HCC (odds ratio 3.69). 84 This supports the premise that OBI may play a synergistic role in the occurrence of HCC in HCV coinfected patients, especially in patients with advanced fibrosis and cirrhosis.…”
Section: Key Pointsupporting
confidence: 78%
“…While there were no clinical differences between patients with and without OBI (gender, serum transaminases, platelet count, albumin, bilirubin, prothrombin time, alphafetoprotein, Child-Pugh score), those with OBI were younger (48.4 year-old for OBI compared to 51.4 year-old for non-OBI), and were associated with more advanced histological grades of HCC (odds ratio 3.69). 84 This supports the premise that OBI may play a synergistic role in the occurrence of HCC in HCV coinfected patients, especially in patients with advanced fibrosis and cirrhosis.…”
Section: Key Pointsupporting
confidence: 78%
“…Analogously, many studies from Asia and Europe have shown that the prevalence of OBI is significantly higher in anti-HCV-positive patients with HCC than in those with CLD or in healthy controls [ 21 , 148 , 149 , 150 , 151 ]. An Egyptian study including anti-HCV-positive patients with HCC who underwent resection or liver transplantation showed that those with OBI (50% of the subjects analyzed) were younger and with a worse histological liver tumor grade [ 152 ]. Two observational cohort studies (with a median follow-up of 6.9 years and 11 years) analyzing the cumulative incidence of HCC in both cirrhotic and non-cirrhotic anti-HCV-positive subjects with and without OBI, showed that OBI carriers had a higher incidence of HCC than patients without OBI [ 128 , 153 ].…”
Section: Clinical Implications Of Obimentioning
confidence: 99%
“…Previous studies have compared the clinicopathological features and prognosis of HCC patients with HBV and HCV infections [17][18][19]. However, both of them are caused by chronic viral infection.…”
Section: Introductionmentioning
confidence: 99%